A qualitative exploration to understand barriers and facilitators to daily oral PrEP uptake and sustained adherence among HIV‐negative women planning for or with pregnancy in rural Southwestern Uganda. Issue 3 (24th March 2022) - Atukunda, Esther Cathyln; Owembabazi, Moran; Pratt, Madeline Claire; Psaros, Christina; Muyindike, Winnie; Chitneni, Pooja; Bwana, Mwebesa Bosco; Bangsberg, David; Haberer, Jessica Elizabeth; Marrazzo, Jeanne; Matthews, Lynn Turner
Abstract: Introduction: Antiretroviral pre‐exposure prophylaxis (PrEP) may reduce periconception and pregnancy HIV incidence among women in settings, where gender power imbalances limit HIV testing, engagement in care and HIV viral suppression. We conducted qualitative interviews to understand factors influencing periconception and pregnancy PrEP uptake and use in a cohort of women (Trial registration: NCT03832530) offered safer conception counselling in rural Southwestern Uganda, where PrEP uptake was high. Methods: Between March 2018 and January 2019, in‐depth interviews informed by conceptual frameworks for periconception risk reduction and PrEP adherence were conducted with 37 women including those with ≥80% and <80% adherence to PrEP doses measured by electronic pill cap, those who never initiated PrEP, and seven of their male partners. Content and dyadic analyses were conducted to identify emergent challenges and facilitators of PrEP use within individual and couple narratives. Results: The median age for women was 33 years (IQR 28, 35), 97% felt likely to acquire HIV and 89% initiated PrEP. Individual‐level barriers included unwillingness to take daily pills while healthy, side effects and alcohol use. Women overcame these barriers through personal desires to have control over their HIV serostatus, produce HIV‐negative children and prevent HIV transmission within partnerships. Couple‐level barriers included nondisclosure, mistrust and gender‐based violence; facilitators included shared goals and perceived HIV protection, which improved communication, sexual intimacy and emotional support within partnerships through a self‐controlled method. Community‐level barriers included multi‐level stigma related to HIV, ARVs/PrEP and serodifference; facilitators included active peer, family or healthcare provider support as women aspired to safely meet socio‐cultural expectations to conceive and preserve serodifferent relationships. Confidence in PrEP effectiveness was promoted by positive peer experiences with PrEP and ongoing HIV testing. Conclusions: Multi‐level forms of HIV‐, serodifference‐ and disclosure‐related stigma, side effects, pill burden, alcohol use, relationship dynamics, social, professional and partnership support towards adaptation and HIV risk reduction influence PrEP uptake and adherence among HIV‐negative women with plans for pregnancy in rural Southwestern Uganda. Confidence in PrEP, individually controlled HIV prevention and improved partnership communication and intimacy promoted PrEP adherence. Supporting individuals to overcome context‐specific barriers to PrEP use may be an important approach to improving uptake and prolonged use.